Strategi Kebijakan Kesehatan di Provinsi Banten - Maulana, Delly (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Health policy in Banten Province must be rooted in the principles of non-discrimination, public participation, and sustainability to ensure inclusive and equitable access to health services. Health is a fundamental need for the people of Banten, and the fulfillment of quality healthcare services is a key factor in achieving public welfare. This paper explores strategic health policies aimed at addressing persistent health issues in Banten Province. A qualitative descriptive approach was employed, using secondary data obtained from government reports, statistical records, and academic literature. The findings reveal that health disparities remain prominent across the northern, central, and southern regions of Banten, especially in terms of health facilities and the availability of medical personnel. Moreover, nutritional deficiencies and the prevalence of stunting among children continue to pose significant challenges. Another crucial issue identified is the unequal distribution and ownership of health insurance across the province. In response, this study proposes four key health policy strategies: (1) strengthening nutrition programs and stunting reduction initiatives; (2) expanding access to health insurance in underserved areas; (3) improving the distribution of healthcare facilities and medical staff, particularly in the southern regions; and (4) enhancing stakeholder collaboration to ensure integrated health service delivery. These strategies are expected to improve the overall health outcomes and resilience of communities in Banten Province, while also supporting long-term sustainable development.